Implementasi Manajemen Risiko Pembiayaan Syariah dalam Upaya Menjaga Likuiditas Koperasi Syariah di BMT Maslahah Cabang Sukorejo Kabupaten Pasuruan - Ulfatul Islamiyah; Abdillah Mundir; Alimatul Farida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study discusses the implementation of Islamic financing risk management in maintaining the liquidity of Islamic cooperatives at BMT Maslahah Sukorejo Branch Pasuruan Regency. Risk management is a crucial aspect of the operational activities of Islamic cooperatives to ensure business continuity and minimize problematic financing risks that could disrupt liquidity stability. This study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. Data analysis is conducted using data reduction, data presentation, and conclusion drawing. The findings indicate that BMT Maslahah implement risk management through identification, measurement, monitoring, and risk control stages. The main strategies involve appliying the 5C principles (Character, Capacity, Capital, Condition, and Collateral) in financing analysis, strict supervision by Account Officer (AO) and Recovery Officer (RO), as well as restructuring policies for customers facing payment diffficulties. The effectiveness of risk management implementation at BMT Maslahah Sukorejo Branch is reflected in the controlled Non-Performing Financing (NPF) rate, maintained liquidity stability, and increased efficiency in financing management. However, challenges remain, such as limited resources for customer assistance, external economic conditions, and the need for innovation in risk mitigation strategies. Therefore, strengthening policies and adopting a more adaptive approach are necessary for the cooperative to continue sustainable growth in accordance with Islamic principles.